The Czech Republic and Slovakia in terms of mortality from malignant neoplasms: similar or opposite tendencies - Hulíková, Klára (Central European Journal of Public Health, 2017)
In Europe, a steady mortality decline has been observed from the 1950s, however, Central and Eastern Europe underwent a period of stagnation or even worsening from the 1960s to 1980s. Since that time an evident mortality decline could be observed in that part of Europe too. Within the post-communist countries, mortality development has been most favourable in Slovenia, the Czech Republic and Slovakia. The aim of this study is to describe the latest development of cancer mortality in two selected countries - the Czech Republic and Slovakia. These two countries have much in common, including many similar long term trends in demographic or social indicators' development. The study evaluates whether cancer mortality development differs in the two countries or rather follows a similar trend. From the presented results it is clear that the development apparently differs namely according to sex. The results according to selected particular causes of death (from the group of malignant neoplasms) are presented as well. It could be assumed that many aspects could be improved by prevention programmes or screening.
Keywords: lidé; mladiství; Adult; Middle Aged; rozložení podle pohlaví; Age Distribution; Slovakia; Infant; Female; Sex Distribution; dítě; Adolescent; Humans; Slovenská republika; Česká republika; předškolní dítě; lidé středního věku; Child, Preschool; věkové rozložení; mužské pohlaví; mladý dospělý; nádory; Czech Republic; ženské pohlaví; Young Adult; Aged, 80 and over; senioři nad 80 let; Male; Aged; Child; dospělí; Neoplasms; kojenec; senioři